Pengembangan Bahan Ajar Berbasis E-Modul pada Pembelajaran Komunikasi Perkantoran Program Studi Pendidikan Administrasi Perkantoran - Nurul Isnaini; Harti Harti; Siti Sri Wulandari; Finisica Dwijayanti Patrikha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2021)
The development research aims to develop E-Module teaching materials in office communication learning, office administration education study programs. In addition, research was conducted to determine the feasibility of e-modules and student responses to the developed e-modules. Thiagarajan's 4-D development model (Define-Design-Develop Desseminate) is used in the development of this e-module. This research was piloted on 20 students of the office administration education study program. The data collection instrument used a material expert validation sheet, a linguist, a media expert and a student response questionnaire sheet. Expert validation sheets and student response questionnaires were analyzed quantitatively using a Likert scale. The results showed the feasibility of expert validation of the e-module teaching materials developed, namely material validation obtained 84.34%, language validation 82.85%, and media validation 86.67% in the very strong interpretation category so that it can be used for learning activities. And the results of student responses obtained an assessment of 84.15% with very strong interpretation criteria.